2019
DOI: 10.1021/acsenergylett.9b01783
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area 23%-Efficient Monolithic Perovskite/Homojunction-Silicon Tandem Solar Cell with Enhanced UV Stability Using Down-Shifting Material

Abstract: UV-induced degradation and parasitic ultraviolet (UV) absorption by the “sun-facing” carrier transport layer in a perovskite cell hinders stability and electrical performance when the perovskite cell is a top cell for a Si-based tandem. In this work, we tackle these issues by applying textured polydimethylsiloxane (PDMS) films that incorporate a down-shifting material (Ba,Sr)2SiO4:Eu2+ micron phosphor on the front of monolithic perovskite/silicon tandem cells. This film serves multiple purposes: antireflective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 59 publications
0
70
0
Order By: Relevance
“…To date, the most efficient perovskite‐based tandem solar cells have been realized using PSCs on top of low‐bandgap c‐Si [ 6,18,21,23,25,34–42,43 ] or thin‐film CIGS ( E g ≈ 1.0–1.2 eV) [ 24,44–49 ] solar cells. [ 4,19,20,50 ] Record PCEs of up to 29.1% (perovskite/c‐Si, 2T), [ 6 ] 27.7% (perovskite/c‐Si, 4T), [ 43,51 ] 23.3% (perovskite/CIGS, 2T), [ 48 ] and 25.9% (perovskite/CIGS, 4T) [ 45 ] have been reported for the different architectures and configurations.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most efficient perovskite‐based tandem solar cells have been realized using PSCs on top of low‐bandgap c‐Si [ 6,18,21,23,25,34–42,43 ] or thin‐film CIGS ( E g ≈ 1.0–1.2 eV) [ 24,44–49 ] solar cells. [ 4,19,20,50 ] Record PCEs of up to 29.1% (perovskite/c‐Si, 2T), [ 6 ] 27.7% (perovskite/c‐Si, 4T), [ 43,51 ] 23.3% (perovskite/CIGS, 2T), [ 48 ] and 25.9% (perovskite/CIGS, 4T) [ 45 ] have been reported for the different architectures and configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The development of tandem device can advance existing technologies and enable versatile exploitation of solar materials. For instance, wide bandgap solar cell coupling with low bandgap silicon or Cu 2 (In,Ga)Se 2 (CIGS) solar cells has been considered as a promising approach to upgrading the well‐established solar technologies . In attempt to achieve low‐cost solar cell applications, tandem solar cells based on emerging materials have also been used, such as those based on polymer–amorphous silicon, organic‐quantum dots hybrid tandem solar cells .…”
Section: Photovoltaic Parameters Of Semitransparent Sb2s3 Cells Withmentioning
confidence: 99%
“…[101] Therefore, the recombination layer exhibits high lateral conductivity, which is associated with shunt pathways. [102,103] As TCO conductivity depends on film thickness and doping concentration, it is important to trade off these two parameters to suppress parasitic absorption by FCA in the TCO film while achieving high conductivity. [45] On the other hand, a TCO layer thickness of several tens of nanometers is sufficient to protect the bottom subcell from damage during the fabrication of the top subcell.…”
Section: Interconnection Layer In Hybrid Tandemsmentioning
confidence: 99%
“…The interlayer-free hybrid tandem was further developed using perovskite absorbing layer improvement and light management to increase PCE to 23.1% with V oc = 1732 mV, J sc = 16.5 mA cm −2 , and FF = 81% for an area of 4 cm 2 . [103,117] Shen et al revealed that TiO 2 deposited by ALD onto p-type Si exhibits a highly ohmic contact to enable the operation of an efficient tandem cell. [118] Subsequently, these authors demonstrated an interlayerfree design with the perovskite layer directly deposited on top of the front emitter of poly-Si and commercial homojunction Si without an additional junction layer.…”
Section: In Situ Recombination Junctionmentioning
confidence: 99%